A Seamless Handover Management for VANETs across Heterogeneous Networks - Singh, Chandrakant Kumar; Shukla, Narendra Kumar (International Journal of Computer Sciences and Engineering, 2021)
Today, Vehicular Ad Hoc Network (VANET) is an emerging technology. Mobility management is the emerging research area in the field of VANET for supporting different aspects of Intelligent Transportation System (ITS) applications. Mobility solutions for VANET can be classified into two categories namely, inter domain and intra domain. Therefore, the mobility management for vehicular networks is required. However most of Mobility model currently used are very simple. In this paper we will focus on the Network Mobility Approach in Vehicular Ad Hoc Network, this model is well suited for highway and city environment, and provides efficient and timely route establishment between the moving vehicles from one network to another network.